ANALISIS PRINSIP-PRINSIP PENGEMBANGAN KURIKULUM PADA LEMBAGA PENDIDIKAN ISLAM - Sumarmi Trina; Achmad Muadin (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Curriculum is the starting point of‘anSeducation. A good curriculum is a curriculum that is based on relevant curriculum development principles. Both relevant to the times, the needs of market prey, and relevant to religion. However, the frequent occurrence of curriculum’changes in Indonesia illustrates that there are still problems in our educational curriculum.SThe purposeSof this research is to find out whether theSAl Hikmah Integrated PAUD Islamic education institution has developed its institutional curriculum based on existing curriculum development principles. The research uses descriptive qualitative methods through questionnaires given to research targets related to the principlesSof curriculum development and literature study toSanalyze research results.SThe results ofSthe analysis of this research are that the Al Hikmah Integrated PAUD Islamic education institution has used curriculum principles both in general and specifically, so that institutions can brand themselves to continue to develop amidst the progress of the times.